2016
DOI: 10.1007/s13139-016-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Open-Mouth Bone Scintigraphy Is Better than Closed-Mouth Bone Scintigraphy in the Diagnosis of Temporomandibular Osteoarthritis

Abstract: Purpose Closed-mouth bone scintigraphy (CM scan) and closed-mouth single-photon emission computed tomography (CM SPECT) are used for conventional evaluation of osteoarthritis of the temporomandibular joint (TMJ). However, the adequacy of open-mouth bone scintigraphy (OM scan) has not yet been evaluated. Therefore, the purpose of this study was to compare the diagnostic performance of CM scan, CM SPECT, and OM scan. Methods Thirty-six patients with suspicion of an abnormality of the TMJ and who underwent a 99m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ultrasound has the advantages of being non-invasive, cheap, and widely available in many health institutions, yet the effectiveness as a diagnostic method remains to be confirmed [ 15 ]. For some inflammatory conditions of the TMJ, such as osteoarthritis and joint inflammation, bone scintigraphy may be of value as a diagnostic tool [ 39 , 40 , 41 , 42 , 43 ]. Moreover, bone scintigraphy has been proposed as a method for the evaluation of active TMJ condylar growth, but it has been shown that both the sensitivity and specificity are low for this indication [ 44 ].…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Ultrasound has the advantages of being non-invasive, cheap, and widely available in many health institutions, yet the effectiveness as a diagnostic method remains to be confirmed [ 15 ]. For some inflammatory conditions of the TMJ, such as osteoarthritis and joint inflammation, bone scintigraphy may be of value as a diagnostic tool [ 39 , 40 , 41 , 42 , 43 ]. Moreover, bone scintigraphy has been proposed as a method for the evaluation of active TMJ condylar growth, but it has been shown that both the sensitivity and specificity are low for this indication [ 44 ].…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…[44,45] Open-mouth bone scintigraphy was proved to be better than closed-mouth bone scan in patients with temporomandibular osteoarthritis as it is difficult to differentiate physiologic bone uptake in a condyle and glenoid fossa of temporal bone in closed-mouth position. [46] bone scintigraphy is not a routinely used technique but studies show that it is useful in diagnosing osteoarthritis of TMJ.…”
Section: Scintigraphymentioning
confidence: 99%
“…There were significant differences in uptake ratios between the osteoarthritis and non-osteoarthritis groups thus leading to a conclusion that bone scans may help to diagnose osteoarthritis when uptake ratios are increased. Open-mouth bone scintigraphy was proved to be better than closed-mouth bone scan in patients with temporomandibular osteoarthritis as it is difficult to differentiate physiologic bone uptake in a condyle and glenoid fossa of temporal bone in closed-mouth position [39].…”
Section: Scintigraphymentioning
confidence: 99%